Letter from Max Bredig to Hans Jolowicz, August 30, 1945 - Bredig, Max Albert (1945)
In this mostly illegible letter from Max Bredig (1902-1977) to Hans Jolowicz (1909-1987), Bredig discusses the investigation of the death of his friend Alfred Schnell (1900-1944) and Jolowicz' sister, Eva Jolowicz Schnell (1913-1944).
Keywords: Bredig, Max Albert, 1902-1977; Schnell, Federico; Jolowicz, Hans, 1909-1987; Schnell, Eva, 1913-1944; Schnell, Alfred, 1900-1944